Tradisi Seloko Ulur Antar sebagai Cerminan Nilai Moral dalam Kehidupan Masyarakat Bernai Luar Provinsi Jambi - Safitri, Tari; Sulistiyo, Urip; Wini, Lusia Oktri (DIKBASTRA: Jurnal Pendidikan Bahasa dan Sastra, 2025)
This study aims to describe and analyze the moral values contained in the Seloko Ulur Antar tradition at the traditional wedding of the Bernai Luar Village community, Sarolangun District, Jambi. This research uses an ethnographic approach with descriptive qualitative methods. Data were obtained through participatory observation, in-depth interviews with two traditional leaders, and direct documentation during the Ulur Antar procession. The results showed that the Seloko Ulur Antar tradition contains moral values conveyed in the form of symbolic language through kato undang, proverbs, traditional rhymes, and kias words. The dominant moral values include politeness, equality, patience, empathy, and respect for local wisdom. This tradition functions as an educative medium and character booster, especially in shaping the social awareness of the younger generation. The novelty of this research lies in the systematic documentation of the form and meaning of seloko and its disclosure as a source of local culture-based character education values. The implications of the moral values in the Ulur Antar tradition show that the preservation of customary traditions in Bernai Luar Village not only strengthens social solidarity and human relations (hablumminannas), but also strengthens religious values (hablumminallah), patience, humility, and respect for local culture as the foundation of community character education.